Answer:
the nth term of the sequence is ![a_n=6n+7](https://tex.z-dn.net/?f=a_n%3D6n%2B7)
Step-by-step explanation:
Given : An arithmetic sequence begins as follows: ![a_1=13, a_2=19](https://tex.z-dn.net/?f=a_1%3D13%2C%20a_2%3D19)
To find : Which of the following gives the definition of its nth term?
Solution :
The nth term of the A.P is ![a_n=a+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da%2B%28n-1%29d)
The first term is ![a=a_1=13](https://tex.z-dn.net/?f=a%3Da_1%3D13)
The common difference is ![d=a_2-a_1](https://tex.z-dn.net/?f=d%3Da_2-a_1)
![d=19-13=6](https://tex.z-dn.net/?f=d%3D19-13%3D6)
Substitute in the formula,
![a_n=13+(n-1)6](https://tex.z-dn.net/?f=a_n%3D13%2B%28n-1%296)
![a_n=13+6n-6](https://tex.z-dn.net/?f=a_n%3D13%2B6n-6)
![a_n=6n+7](https://tex.z-dn.net/?f=a_n%3D6n%2B7)
Therefore, the nth term of the sequence is ![a_n=6n+7](https://tex.z-dn.net/?f=a_n%3D6n%2B7)